ASSESSMENT OF THE EDUCATIONAL VALUES OF GEOMORPHOSITES BASED ON THE EXPERT METHOD, CASE STUDY: THE BIAŁKA AND SKAWA RIVERS, THE POLISH CARPATHIANS - Chrobak, Anna; Witkowski, Karol; Szmańda, Jacek (Quaestiones Geographicae, 2020)
Geotourism is a type of qualified tourism promoting geosites related to the geological outcrops and relief elements, such as river channels. Examples of these landforms with high educational values can be seen in the Białka and Skawa riverbeds. However, an important element in the description of such geosites (geomorphosites) is their educational values, which make it possible to clearly determine their suitability and possible use in geotourism. The assessment methods are the only methods of evaluating these values. But they are subjective, and the results of the analyses carried out on them largely depend on the knowledge and experience of the evaluator. In this paper, four geomorphosites have been assessed using the triangulation expert method. All described geomorphosites have received a high educational value, and the highest had the Białka Gorge.